Iron Sharpens Iron Social Interactions at China Shops in Botswana - Zi, Yanyin; Zi, Yanyin (Langaa RPCIG, 2017)
For centuries the continent of Africa has been characterised by negative images such as poverty, disease and conflicts. Today, however, the People?s Republic of China?s growing presence in Africa, particularly with regards to China?Africa business relations, brings new vitality to the continent. This new movement is not a windfall but rather obtained through the hard work of both African and Chinese people at various levels. Narrating on daily experiences of Chinese merchants and their vivid interactions with people in Botswana, this book decodes the frustrating while rewarding process through which China?Africa relations have been maturing on the grass-roots level. This book not only presents insights and suggestions to both Botswana and Chinese policy makers interested in understanding their constituents? everyday interactions with each other, but also offers readers interested more broadly in contemporary Chinese experiences in Africa a fascinating glimpse into these cross-cultural encounters. This book is an original and pioneering study of issues that resonate in almost every African country which has responded to a growing Chinese presence. It argues that as the process of globalisation permeates the everyday lives of people, each individual is empowered to be an ?ambassador? in shaping international relations.